Summary of the Pi of the Sky photometry improving methods - Opiela, R.; Malek, K.; Mankiewicz, L.; Siudek, M.; Sokolowski, Marcin; Zarnecki, A. (2014)
© 2014 SPIE.Pi of the Sky is a system of five wide field of view robotic telescopes, which search for short timescale astrophysical phenomena, especially for prompt optical GRB emissions. The system was designed for autonomous operation, monitoring a large fraction of the sky with 12m - 13m range and time resolution of the order of 1-10 seconds. Five fully automatic Pi of the Sky detectors located in Spain (INTA - INTA El Arenosillo Test Centre in Mazagón, near Huelva.) and Chile (SPDA - San Pedro de Atacama Observatory.) have been observing the sky almost every night in search of rare optical phenomena. They also collect a lot of useful observations which include e.g. observations of many kinds of variable stars. To be able to draw proper conclusions from the data received, adequate quality of the data is very important. Unfortunately Pi of the Sky data is subject to systematic errors caused by various factors, such as cloud cover, seen as significant fluctuations in the number of stars observed by the detector, problems with conducting mounting, a strong background of the Moon or the passing of a bright object, e.g. a planet, near the observed star. Some of these adverse effects can be easily detected during the cataloging of individual measurements, but the quality of our data was still not satisfactory for us. In order to improve the quality of our data, we have developed two new procedures based on two different approaches. In this article we will report on these procedures, give some examples, and show how these procedures improve the quality of our data.1 Later we will compare developed methods, give they advantages and disadvantages and show how we can obtain the best data quality, based only on the best combination of used algorithms results. At the end of this article we will describe how these corrections improve the period detection error, what is the most important result when we want to obtain the physical parameters of the analyzed stars.